A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

School counseling: Partnering with a school district to provide postsecondary opportunities for first generation, low income, and students of color - Perusse, Rachelle; Deronck, Nicole G; Parzych, Jennifer (Psychology in the Schools, 2017)
A classroom activity led by district school counselors was conducted in a K-12 school district to ensure educational equity for students in relation to postsecondary attendance. This took place in a school setting that has a large population of students of color, predominately Latino and African American students, as well as low-income students. As part of their practicum field experience, university school counseling students were supervised by school counselors at their sites to help provide a readily available and modified curriculum to instruct students about their options related to postsecondary awareness, planning, and attendance, as well as demonstrate career pathways that engender high expectations and college and career readiness. Instruction took place in the classroom as well as in small group settings.
Keywords: dept.csp; peer-reviewed; postsecondary opportunities

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Implementing the developmental school counseling core curriculum in the classroom - Perusse, R.; Parzych, Jennifer L.; Erford, Bradley T. (Transforming the School Counseling Profession, 2018)
Transforming the way thousands of professional school counselors approach their work with students Transforming the School Counseling Profession demonstrates how to effectively implement systemic, data-driven school counseling programs.This clearly written text presents the profession in easy-to-understand language, and is illustrated with numerous applied examples, case studies, and vignettes. The 5th Edition has been updated to include all of the latest CACREP, ASCA, and ACA standards. It also now includes the DSM-5. Coverage of cultural competence has been expanded throughout the book. Also available with MyLab Counseling MyLab is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. MyLab Counseling organizes all assignments around essential learning outcomes and the CACREP standards–enabling easy course alignment and reporting. Note: You are purchasing a standalone product; MyLab Counseling does not come packaged with this content. Students, if interested in purchasing this title with MyLab Counseling, ask your instructor to confirm the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information. If you would like to purchase both the physical text and MyLab Counseling, search for: 0134669843 / 9780134669847 Transforming the School Counseling Profession plus MyLab Counseling with Enhanced Pearson eText -- Access Card Package Package consists of:       0134610598 / 9780134610597 Transforming the School Counseling Profession 0134642651 / 9780134642659 MyLab Counseling with Enhanced Pearson eText -- Access Card -- for Transforming the School Counseling Profession
Keywords: dept.csp